Exchange rate regimes, devaluations and growth collapses - Bleaney, Michael; Saxena, Sweta; Yin, Lin (Elsevier, 2018)
The loss of output in major recessions tends to be permanent. Using IMF de facto exchange rate regime classifications over the period 1980 to 2012 for up to 193 countries, it is shown that growth collapses are more frequent under less flexible exchange rate regimes, and particularly hard pegs. Amongst intermediate regimes, those with recent devaluations are less likely to experience a growth collapse, which confirms the role of exchange rate adjustment in reducing the output effects of a negative shock. Our findings are robust to the marked shift in the pattern of growth collapses after the global financial crisis.